Numerical Approximation of Internal Temperature in the Cylinder of an IC Engine - Dastoor Mirkalaei, Hatef; Karamali, Gholamreza (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this study, mollification and marching methods are used to solve an inverse problem in combustion engines. With the benefit of 2D mollification, we first propose an algorithm, and then prove some theorems, which ensure us the proposed method in stable and reliable, and then some numerical experiment has been done to show the efficiency of the method.